Can investor attention defuse the risk of corporate zombification? Empirical evidence from listed companies in China - Yan Lin; Xinjing Zhang (Journal of Business Economics and Management (JBEM), 2023)
Solving the risk of zombification of enterprises and relieving their business difficulties, as a key element of supply-side structural reform, is the pain point of the conversion of old and new dynamic energy and the difficulty of economic transformation and upgrading. In the Internet era, the impact on business operations is also expanding with the widening of investor attention channels. This paper selects Chinese listed companies from 2011-2020 as a research sample, and the empirical results show that, first, investor attention can effectively reduce the risk of transforming enterprises into zombie enterprises, i.e., the risk of corporate zombification decreases as the level of investor attention increases; second, there is heterogeneity in the role of investor attention in resolving the risk of corporate zombification; third, further mechanism tests find that along with Third, further mechanistic tests reveal that as the level of investor attention increases, the level of environmental uncertainty decreases and the annual market value of individual stocks increases, thereby reducing the risk of corporate zombification. The findings of this paper provide theoretical support and empirical evidence for further improving the risk mitigation of corporate zombification, promoting the "de-emphasis" of enterprises, and leading the high-quality and healthy development of enterprises.
Keywords: G4; M1; 650; business management; empirical studies; investor focus; mechanism of action; probit model; zombie enterprises